The effect of franchise no-poaching restrictions on worker earnings - Callaci, Brian,Gibson, Matthew,Pinto, Sérgio,Steinbaum, Marshall,Walsh, Matt (W.E. Upjohn Institute for Employment Research, 2024)
We evaluate the nationwide impact of the Washington State attorney general's 2018-2020 enforcement campaign against no-poach clauses in franchising contracts, which prohibited worker movement across locations within a chain. Implementing a staggered difference-indifferences research design using Burning Glass Technologies job vacancies and Glassdoor salary reports from numerous industries, we estimate a 6 percent increase in posted annual earnings from the job vacancy data and a 4 percent increase in worker-reported earnings.
10.17848/wp24-405
Keywords: Graue Literatur; Employer market power; oligopsony; monopsony; franchising chains; antitrust; wages; salaries